1984
DOI: 10.1002/asi.4630350205
|View full text |Cite
|
Sign up to set email alerts
|

Search interview techniques and information gain as antecedents of user satisfaction with online bibliographic retrieval

Abstract: The purpose of this research study was to undertake a systematic investigation into the relationships among:(1) the techniques used by search analysts during preliminary interviews with users before engaging in online retrieval of bibliographic citations; (2) the amount of new informatlon gained by the user as a result of the search; and (3) the user's ultimate satisfaction with the quality of the items retrieved. A series of controlled ex. periments were conducted to explore the effects of two interview techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…22 Consistent with previous findings, this study also found that user satisfaction was higher when librarians demonstrated listening behaviors than when they did not. Cordial and receptive listening also was found to be a significant positive predictor of user satisfaction.…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…22 Consistent with previous findings, this study also found that user satisfaction was higher when librarians demonstrated listening behaviors than when they did not. Cordial and receptive listening also was found to be a significant positive predictor of user satisfaction.…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…Many studies have focused on the benefits of librarians asking open questions with little structure as opposed to closed questions with a tight structure during reference interviews (Katz, 1987;King, 1972;Lynch, 1978;McFayden, 1975;Taylor, 1968). Researchers have examined many aspects of online reference interviews, including neutral questioning (Dervin & Dewdney, 1986), evaluation of intermediaries' communication behavior (Auster & Lawton, 1984;Markey, 1981), and dialogue between search intermediaries and patrons (Cochrane, 1981;Crouch & Lucia, 1981;Horne, 1990;Ingwersen, 1982). Brooks (1986) investigated the features of an intelligent interface simulating the functional behavior of a good search intermediary.…”
Section: Search Intermediary Elicitationsmentioning
confidence: 99%
“…Studies of the search interviews that intermediaries conduct with patrons before conducting online 1 See for example, the National Agricultural Library InterNic service provides an HTML form modeled on reference interview templates (http://www.agnic.org/orsp/) and the Virtual Reference Desk (http://www.vrd.org/) provides online reference support. searches (e.g., [4]) and investigations of professional intermediaries actually conducting searches in online databases (e.g., [7]) demonstrate the conceptual challenges of reference services. More than a decade of research at MIT on the Intrex and Conit systems to automate online searching (e.g., [15]) illustrates the complexities of online interactions and the need for user support in using online services.…”
Section: Sharing Time and Expertisementioning
confidence: 99%
“…Additionally, these tools will help creators consider storage and retrieval issues at the time of creation rather than as add-ons after the fact (e.g., tools may assist in adding metadata, provenance, and citations), and specify user options such as display modes, language translations, and required sequences or related materials. Just as the WWW has allowed anyone with Internet access to publish simple web pages, a sharium will allow anyone to "check out" and use style sheets, XML DTD's, and other templates to facilitate creation and contribution of new products 4 . These capabilities will expand DL service to the creation phase of the information life cycle.…”
Section: Using Information and Learningmentioning
confidence: 99%